2018
DOI: 10.1016/j.conbuildmat.2018.05.253
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between bending test and Barcelona tests to determine FRC properties

Abstract: The use of fiber reinforced concretes (FRC) as a substitute for reinforcement meshes, particularly in the construction of tunnels, frequently faces quality control problems because the specifications and acceptability criteria are based on parameters obtained from the flexion test of standard EN-14651, which is very difficult to perform at works. Considering the advantages presented by the Barcelona test, in this paper, equivalences are established between both tests, which allow estimating the FRC toughness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
(12 reference statements)
0
9
0
3
Order By: Relevance
“…Similarly, it may be due to the fact that great care was taken before the test, by placing metal plates to ensure a continuous contact between the panels and the support; and during spraying, avoiding buckling on the panels. Several authors report that CV decreases with enhancing the fracture surface (Carmona et al 2018). Nonetheless, the CV increases in the mixture with higher fibre content.…”
Section: Comparison Of Coefficients Of Variationmentioning
confidence: 97%
“…Similarly, it may be due to the fact that great care was taken before the test, by placing metal plates to ensure a continuous contact between the panels and the support; and during spraying, avoiding buckling on the panels. Several authors report that CV decreases with enhancing the fracture surface (Carmona et al 2018). Nonetheless, the CV increases in the mixture with higher fibre content.…”
Section: Comparison Of Coefficients Of Variationmentioning
confidence: 97%
“…In this way, Galeote et al (2017) found that the best correlations relate the force measured for a certain value of crack mouths opening displacement ( ) in the 3PB test with the force and the energy for the same axial displacement measured in the BCN. On the other side Carmona et al (2018) proposed correlations based on crack opening ( ). This deformation had been also used by Conforti et al (2017) to correlate 3PB test (EN 14651) and 4PB test (ASTM C 1609).…”
Section: Equivalence Between Flexural and Double-punch Crackingmentioning
confidence: 99%
“…Os resultados são apresentados em um gráfico de Carga versus CMOD para teor estudado, considerando as cargas com 0,5 mm, 1,5 mm, 2,5 mm e 3,5 mm de abertura de fissura como parâmetros para avaliação do CRF. TOALDO, FIGUEIREDO, 2014;SILVA et al, 2015;MONTE et al, 2016;SIMÃO et al, 2017;NOGUEIRA et al, 2017;GALEOTE et al, 2017;CARMONA, AGUADO, MOLINS, 2018  GRUPO B: outros elementos estruturais de CRF (elementos lineares, elementos de superfície e elementos de volume).…”
Section: Efeito Sobre a Consistênciaunclassified
“…A matriz de concreto, sem adição de fibras, foi igual para as duas macrofibras e, portanto, os resultados estão apresentados apenas na Tabela 3-3. importante notar que a resistência no limite de proporcionalidade (fL), considerando todos os concretos produzidos foi na média igual a 4,39 MPa. Esse valor está em acordo com o indicado na Prática recomendada IBRACON/ABECE (2017b), 21%, é compatível com a observada por outros autores(MAIDA et al, 2015;CARMONA, MOLINS, AGUADO, 2018;CONFORTI, ZERBINO, PLIZZARI, 2018). Tabela 3-6 que os valores fL não sofreram grande variação para os diferentes teores de fibra analisados.…”
unclassified